2021
DOI: 10.1186/s13071-020-04567-4
|View full text |Cite
|
Sign up to set email alerts
|

Red and fallow deer determine the density of Ixodes ricinus nymphs containing Anaplasma phagocytophilum

Abstract: Background The density of Ixodes ricinus nymphs infected with Anaplasma phagocytophilum is one of the parameters that determines the risk for humans and domesticated animals to contract anaplasmosis. For this, I. ricinus larvae need to take a bloodmeal from free-ranging ungulates, which are competent hosts for A. phagocytophilum. Methods Here, we compared the contribution of four free-ranging ungulate species, red deer (Cervus elaphus), fallow deer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…With their habitat preferences and the circadian rhythm of feeding and resting phases, C. capreolus roe deer are easily accessible and preferable tick hosts. Additionally, previous studies have shown a correlation between the density of local populations of C. capreolus and the incidence of tick-borne diseases in humans [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…With their habitat preferences and the circadian rhythm of feeding and resting phases, C. capreolus roe deer are easily accessible and preferable tick hosts. Additionally, previous studies have shown a correlation between the density of local populations of C. capreolus and the incidence of tick-borne diseases in humans [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anaplasma phagocytophilum is usually detected in 0.7% to 33.9% of the questing ticks, with a highly diverse prevalence between countries [ 4 , 29 , 30 , 31 ]. Clinical cases are sporadically presented in Austria [ 32 ].…”
Section: Discussionmentioning
confidence: 99%